The shifting landscape of prime ministerial accountability to parliament: An analysis of Liaison Committee scrutiny sessions. (August 2016) - Kelso, Alexandra; Bennister, Mark; Larkin, Phil
Prime ministerial power is always contingent, based on the utilisation of personal and institutional resources, subject to various formal and informal constraints. Parliament is both a political resource to be utilised, but also a veto-player. In the absence of formal mechanisms setting out the requirements for the UK prime ministerial accountability to parliament, a fluid and essentially personalised relationship has developed. Regular prime ministerial appearances before the House of Commons Liaison Committee, begun in 2002, have added to parliament's scrutiny toolkit. This article considers the accountability of the prime minister to parliament by analysing the emergence and development of the Liaison Committee evidence sessions, and draws on interviews with participants and examination of the session transcripts, in order to assess the value of this scrutiny mechanism within the broader framework of prime ministerial-legislative relations.